PERLAKUAN AKUNTANSI ZAKAT BERDASARKAN PSAK 45 DAN PSAK 109 PADA BAMUIS BNI - Erika Amelia; Maria Qibtiyah (Faculty of Economics and Business, 2015)
Zakat Institutions Bamuis BNI is one of zakat institution which has been confirmed by the government as an institution of national zakat. Turner is doing charity fund raising and donation / charity, charity funds and donation / charity, and to report accountable. The problems examined is how the accounting treatment of zakat by IAS 45 with SFAS 109. The objective of this study was to determine the accounting treatment of zakat in BAMUIS BNI is based on IAS 45 with SFAS 109. As this study used a qualitative descriptive approach and techniques of data collection through literature research, field research; interviews, documentation. Data analysis was performed simultaneously with data collection. In this analysis describe the data in the accounting treatment of zakat obtained from BAMUIS BNI, the analysis is done by looking at the charity accounting treatment in accordance with SFAS 45 with SFAS 109 on BAMUIS BNI. The study states that there are some differences in the accounting treatment of zakat in accordance with SFAS 45 and 109 on BAMUIS BNI, namely; There are elements of sharia, the burden of the collection and distribution of zakat to be taken from the portion of amyl, the existence of accounts receivable distribution, zakat funds; fund donation / charity; and funds amyl presented separately in the balance sheet, the existence of non-kosher funds, and there is a component of financial statements that are not owned by IAS 45 is the statement of changes in assets under management.